The Power of Conformity: Music, Sound, and Vision in Back to the Future - Marc Priewe (European Journal of American Studies)
This essay investigates the aesthetic and political functions of the choice and placement of music in Back to the Future (1985; dir. Robert Zemeckis). After an overview of the movie’s cultural contexts, the focus shifts to the interplays between sound and cinematic mise-en-scène, with a particular emphasis on popular music. I argue that the film employs music strategically in order to convey a nostalgic view of American culture and society in the 1950s by including certain songs and excluding others, as well as by a score that is deeply rooted in the traditions of Hollywood film music. The intermedial use and remediation of music not only amplifies the movie’s quasi-philosophical treatment of time and history in intricate ways, it also resonates with the contemporary sense of American exceptionalism.